Four centuries of the brothers nodal voyage to Tierra Del Fuego (1618-1619) Cuatro siglos del viaje de los hermanos nodal a La Tierra Del Fuego (1618-1619) - Mateo Martinic, B. (My University, 2019)
This article aims to reminisce what was the shortest and happiest of Spanish expeditions to the New World in its time, however, perhaps it has been the one most forgotten by posterity: the one that was put under the command of Captain Bartolomé García de Nodal and made by order of King Philip III with the order to verify the Dutch find of 1616 referred to a new passage for navigation between the seas of the North and South, and that occurred between 1618 and 1619. For this purpose a succinct relation on its antecedents, organization and the maritime trip itself, and some considerations about its results appreciated from different aspects are included. In particular, reference is made to the first circumnavigation of Tierra del Fuego and the significance of its main geographical finding, such as the discovery of the Diego Ramírez Islands. This insular territory is the subject of a special assessment as an exceptional natural heritage due to its extreme geographical position on the southern edge of the american continental shelf. Este artículo tiene por objeto rememorar la que en su época fuera la más breve y feliz de las expediciones españolas al Nuevo Mundo, sin embargo de lo cual quizá ha sido la más olvidada por la posteridad: aquella que fuera puesta al mando del capitán Bartolomé García de Nodal y realizada por orden del rey Felipe III con el encargo de verificar el hallazgo holandés de 1616 referido a un nuevo paso para la navegación entre los mares del Norte y del Sur, y que tuvo ocurrencia entre 1618 y 1619. Para ello se hace una relación sucinta sobre sus antecedentes, organización y el viaje marítimo propiamente tal, y se incluyen algunas consideraciones acerca de sus resultados apreciados desde distintos aspectos. En particular se hace referencia a la primera circunnavegación de la Tierra del Fuego y al significado de su principal hallazgo geográfico como fuera el descubrimiento de las islas Diego Ramírez. Este territorio insular es materia de una especial valoración como patrimonio natural excepcional por su posición geográfica extrema en el borde meridional de la plataforma continental americana.
Keywords: cabo de hornos; cape horn; circunnavegación fueguina; diego ramírez islands; extreme nature; fuegian circumnavigation; islas diego ramírez; natural patrimony; naturaleza extrema; patrimonio natural; tierra del fuego; tierra del fuego